BIOM-59. NOVEL BIOMARKER DISCOVERY AND DIAGNOSTICS FOR INTRA-AXIAL BRAIN TUMORS, USING CSF PROTEOMICS. (14th November 2022) - Mansouri, Alireza; Mikolajewicz, Nicholas; Khan, Shahbaz; Trifoi, Mara; Zacharia, Brad; Glantz, Michael; Zadeh, Gelareh; Kislinger, Thomas
Abstract: BACKGROUND: Invasive brain sampling is typically necessary for reliable diagnosis and prognostication of intra-axial brain tumors but carries risk of morbidity. Liquid biopsy of proximal fluids may mitigate this risk. Through direct contact with the tumor microenvironment and, as an ultra-filtrate of plasma, the cerebrospinal fluid may be the ideal matrix. Reflecting the tumor phenotype, proteomic analyses are critical. Here we identified diagnostic CSF proteomic signatures and putatively novel biomarkers for glioblastoma (GBM), brain metastases (BM), and central nervous system lymphoma (CNSL). METHODS: CSF samples were retrospectively retrieved from the Penn State Neuroscience Biorepository and profiled using shotgun proteomics and the MStern approach. Proteomic signatures were identified using machine learning classifiers and survival analyses. RESULTS: With as little as 30 µL of CSF, 755 unique proteins were recovered across 73 samples (22 GBM, 17 BM, 14 CNSL, 20 NPH). Proteomic-based classifiers identified malignancy with area under the receiver operating characteristic (AUROC) of 0.94 and distinguished between tumor entities with AUROC ≥0.95. More clinically relevant triplex classifiers, comprised of just 3 proteins, distinguished between tumor entities with AUROC of 0.75-0.89. Novel biomarkers were identified, including GAP43, TFF3 and CACNA2D2, and characterized using single-cell RNA sequencing. DISCUSSION: Reliable classification of intra-axial malignancies using low CSF volumes is feasible, allowing for longitudinal tumor surveillance. Based on emerging evidence, upfront implantation of CSF reservoirs in brain tumor patients warrants consideration.